Placement of replace select Ti-Unite-coated type implants using a combination of immediate and submerge techniques after tooth extraction - Coen Pramono D (Dental Journal (Majalah Kedokteran Gigi), 2006)
The high success rate of immediate implant placement both in the anterior and posterior regions were reported by many authors, therefore applying this techniques can be considered as a safe surgical procedure and minimizing the dental office visit for patient satisfaction. This paper reports the outcome of immediate placement of implants following extraction of anterior maxillary teeth. Combination technique of immediate and submerge implant placements including bone grafting procedure were used. Four implants with TiUnite surface type were placed immediately in two patients with the short-term result indicated that this technique may serve as a simple and safe procedure for immediate implant placement. It was concluded that immediate implant placement technique combined with TiUnite implant surface was successful in treating region directly after tooth extraction therefore this technique can be use as an alternative surgical method for dental implant rehabilitation.